2016
DOI: 10.1557/adv.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Response to Atmospheric Air Plasma Treatments of Seeds of 5 Plant Species

Abstract: We have investigated plant growth response to atmospheric air plasma treatments of seeds on their growth for 5 plant speces; Radish sprout (Raphanus sativus L.), rice (Oryza Sativa), Zinnia, Arabidopsis L. Thaliana and Plumeri. The average length of Radish sprout, rice, Arabidopsis Thaliana, Plumeria and Zinnia, are 250%, 80%, 60%, 30% and 20% longer than those without plasma treatments, respectively. We have obtained correlation between the growth enhancement and O 3 and NO x concentration. The optimum radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In this field, scientists have observed that plasmas are able to sanitize food products and decontaminate plant seeds, fruits, and vegetables [5,[10][11][12]. Several authors have reported the efficient improvement of the germination and growth of agriculturally relevant plant species such as wheat [13][14][15][16][17][18][19][20][21][22][23][24], maize [14,25], lupine [14], soya beans [26,27], mung beans [28], radish [29][30][31], pea [32][33][34][35], and rice [29,36]. It has been shown that exposure to plasma improves water uptake by the seed [34,37], decreases the contact angle of the seed surface [23,37], and functionalizes the seed coat by attaching new chemical bonds to the surface [34,38].…”
Section: Introductionmentioning
confidence: 99%
“…In this field, scientists have observed that plasmas are able to sanitize food products and decontaminate plant seeds, fruits, and vegetables [5,[10][11][12]. Several authors have reported the efficient improvement of the germination and growth of agriculturally relevant plant species such as wheat [13][14][15][16][17][18][19][20][21][22][23][24], maize [14,25], lupine [14], soya beans [26,27], mung beans [28], radish [29][30][31], pea [32][33][34][35], and rice [29,36]. It has been shown that exposure to plasma improves water uptake by the seed [34,37], decreases the contact angle of the seed surface [23,37], and functionalizes the seed coat by attaching new chemical bonds to the surface [34,38].…”
Section: Introductionmentioning
confidence: 99%
“…Authors have pointed the main role of radicals correlated with O 3 and NOx (nitrogen oxides) concentration, strongly indicating that optimum conditions depended on the species. They have also claimed the negligible influence of ions and photons [ 53 , 60 ]. Ono et al, 2017 have investigated positive inactivation effect of low-pressure RF oxygen and air plasmas on cabbage seed-borne bacteria: Xanthomonas campestris pv .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on plasma application in agriculture have demonstrated that the etching effect of O radicals plays an important role in plant growth enhancement. 17,18,[23][24][25][26][33][34][35][36][37][38] The CI was adopted to evaluate the oxidation efficiency of SA1011-3…”
Section: Characteristics Of Lf-microwave Hybrid Plasmamentioning
confidence: 99%
“…Recently, it was reported that the irradiation of atmospheric pressure non-thermal plasma on seeds and water for hydroponic improved seed germination and plant growth. [12][13][14][15][16][17][18][19][20][21][22] Atmospheric pressure non-thermal plasma is characterized by electrons having much higher energy than the ions or atoms, and this higher energy of electrons can produce sufficient reactive species, which allows many types of plasma surface processing without thermal damage. Reactive species produced by atmospheric pressure non-thermal plasma are considered to contribute to reducing pathogenic contamination and stimulating plant growth.…”
Section: Introductionmentioning
confidence: 99%